A qualitative structure activity relationship (SAR) study of selected pyroglutamates (Journal of Bangladesh Academy of Sciences, 2024)
A library of Pyroglutamate derivatives (Fig. 1-4: 8a-8f, 9a-9d, 10a-10e, 11a-11f, 12a-12c, 13 and 14) have been analysed qualitatively to investigate their Structure Activity Relationships (SAR). Antibacterial screening data used for this work was against the selected multidrug-resistant pathogens including both Gram-negative and Gram-positive bacteria. Among the synthesized compounds, pyroglutamates 8e and 11d are more potent as antibacterial agent.J. Bangladesh Acad. Sci. 48(2); 165-170: December 2024